Adverse childhood experiences and related outcomes among adults experiencing homelessness: a systematic review and meta-analysis. (November 2021) - Liu, Michael; Luong, Linh; Lachaud, James; Edalati, Hanie; Reeves, Aaron; Hwang, Stephen W
Summary: Background: Adverse childhood experiences (ACEs) are strong risk factors for homelessness and poor health and functioning. We aimed to evaluate the lifetime prevalence of ACEs and their associations with health-related and functioning-related outcomes among homeless adults. Methods: In this systematic review and meta-analysis, we searched from database inception to Nov 11, 2020, for original and peer-reviewed studies in English that documented lifetime prevalence of ACEs or associations between ACEs and health-related or functioning-related outcomes. We selected studies if they included a definable group of homeless adults and measured at least four ACE categories. We calculated pooled estimates of lifetime prevalence of one or more ACEs and four or more ACEs with random-effects models. We used the leave-one-out method in sensitivity analyses and studied meta-regressions to explore potential moderators of ACE prevalence. We also did a narrative summary of associations between ACEs and health-related and functioning-related outcomes, as there were too few studies on each outcome for quantitative meta-analysis. This study is registered with PROSPERO, CRD42020218741. Findings: We identified 2129 studies through systematic search, of which 29 studies (16 942 individuals) were included in the systematic review, 20 studies (10 034 individuals) were included in the meta-analysis for one or more ACEs, and 15 studies (5693 individuals) were included in the meta-analysis for four or more ACEs. Studies included samples of adults experiencing homelessness in the USA, Canada, and the UK; participants in the included studies were predominantly male (65·2%) and mean ages ranged between 18·3 and 58·1 years, but many studies did not report race, ethnicity, and sexual and gender minority data. Lifetime prevalence of one or more ACEs among homeless adults was 89·8% (95% CI 83·7–93·7) and the lifetime prevalence of four or more ACEs was 53·9% (45·9–61·7). Considerable heterogeneity was identified in both meta-analyses ( I 2 >95%). Of the potential moderators analysed, the ACE measurement tool significantly moderated the estimated lifetime prevalence of one or more ACEs and four or more ACEs, and age also significantly moderated the estimated lifetime prevalence of four or more ACEs. In the narrative synthesis, ACEs were consistently positively associated with high suicidality (two studies), suicide attempt (three studies), major depressive disorder (two studies), substance misuse (two studies), and adult victimisation (two studies). Interpretation: The lifetime prevalence of ACEs is substantially higher among homeless adults than among the general population, and ACE exposure might be associated with prevalence of mental illness, substance misuse, and victimisation. Policy efforts and evidence-based interventions are urgently needed to prevent ACEs and address associated poor outcomes among this population. Funding: Rhodes Trust and Canadian Institutes of Health Research.